FBR for Polyolefin Production in Gas Phase: Validation of a Two‐Phase Compartmentalized Model by Comparison with CFD. Issue 6 (23rd February 2022) - Sabia, Carmine; Buffo, Antonio; Casalini, Tommaso; Marchisio, Daniele L.; Barbato, Maurizio C.; Storti, Giuseppe
Abstract: Two different modeling approaches are applied in this work to the simulation of fluidized bed reactors containing solid particles of Geldart A‐B type and operated at typical conditions for polyolefins production. On one side, a fully detailed computational fluid‐dynamics (CFD) model is developed, considering a 2D planar geometry and a multi‐fluid description with kinetic theory of granular flows. On the other, a conventional three‐phase, 1D compartmentalized model (SCM) is also developed, implementing the fluid dynamic description based on popular, semi‐empirical relationships available in the literature. Given the huge difference of computational effort associated with the corresponding numerical solutions, our aim is to confirm the reliability of the simplified model by comparison with the results of the detailed CFD model. The results show that the oversimplified compartmentalized approach is capable to predict the solid mixing features established inside the reactor operated in bubbling fluidization regime with good reliability for non‐reactive polyethylene particles. Average solid volume fractions are particularly close to the values predicted by the CFD model when monodisperse particles are considered inside the examined range of gas velocity values. A generally good agreement is also found when solids with broad size distribution are analyzed. Abstract : Two different approaches are used to simulate the fluidization behavior of Geldart A–B particles in fluidized bed reactors operated in the bubbling regime. 2D computational fluid dynamics Euler‐Euler predictions are compared to results of a compartment‐based model with simplified fluid‐dynamics description. The compartmentalized approach is appropriate for describing the particle volume fraction and size distribution along the reactor axis.